The role of avalanche education in assessing and judging avalanche risk factors - Markus Landrø; Rune Engeset; Gerit Pfuhl (Cappelen Damm Akademisk NOASP, 2022)
Avalanche decision-making falls into two general categories; probabilistic approaches and analytical approaches. Analytical approaches have traditionally been considered applicable to experts only, as they require assessing risk factors precisely and understanding their relevance in each situation. In this study we question this assumption. We asked 1, 220 amateur backcountry recreationalists how relevant they rated and how precisely they could assess 11 avalanche risk factors. We investigated how their avalanche education and experience with avalanche incidents influenced their judgment of precision and relevance, and if avalanches become more predictable with more knowledge. Most recreationalists considered avalanches as predictable. These five factors were judged as highly relevant: signs of instability, distinguishing avalanche terrain from non-avalanche terrain, slope inclination, terrain traps, and distribution of weak layers. Relevance was independent of avalanche education and experience of incidents for all factors but danger level. Amateur recreationalists rated the relevance of the factors like that of experts. Rating of precision increased with more avalanche education, in particularly for these factors: distribution of the weak layers, terrain traps, avalanche size, recognizing avalanche terrain and stopping at safe spots. We recommend adopting an analytical approach for amateur backcountry recreationalists and discuss implications for avalanche forecasting and education.